Development of live worksheets-assisted discovery learning materials on two-variable linear equation systems - Halomoan, Adil; Rangkuti, Ahmad Nizar; Suparni, Suparni (LINEAR: Journal of Mathematics Education, 2025)
The fast development of technology contributes significantly to education and the production of quality and sustainable human resources. The application of technology in learning is critical to achieving learning objectives and improving student learning outcomes. One of the things that can be used from technology is the creation of learner work exercises in learning. This study aims to determine the validity, practicality, and effectiveness of discovery learning-based student worksheets assisted by live worksheets on the material of the linear equations of a variables system. The type of research used is the Borg and Gall research and development model, consisting of research and initial data collection, planning, development of initial product formats, initial trials, product revisions, field trials, product revisions, field tests, final product revisions, dissemination, and implementation. The instruments used in the research are observation, interviews, questionnaire distribution, tests, and documentation. The results of the research with the development of discovery learning-based student worksheets assisted by live worksheets on the material of the system of linear equations of two variables, among others: (1) the average percentage of validity of student worksheets in terms of language, material and media is 74% with valid criteria, (2) the average percentage of practicality of student worksheets based on teacher and student responses is 86% with very practical criteria, (3) while the average value of learning outcomes in the effectiveness test of student worksheets based on tests conducted is 84 with a percentage of completeness of 87% including a very effective category.